Sustainability of exclusive breast feeding among primigravida women: a hospital based study in eastern India - Choudhuri, Moitreyee; Roy, Gopa; Kamilya, G. S. (International Journal Of Community Medicine And Public Health, 2023)
Background: EBF for 6 months is a challenge for many mothers. The WHO reported the prevalence of EBF lasting at least 6 months as 38% in 2013 and most recently reported as 44% in 2021. As a result, the WHO has set strategic goals for 6-month EBF to achieve 70% prevalence worldwide by 2030. Methods: Descriptive survey research design was used, with the variables as sustainability of Exclusive Breast Feeding among 100 postnatal primi gravida attending a tertiary care hospital in Eastern India. Sampling technique was Systemic random sampling technique. Standardized tool (Feed Cat Tool) was used as a data collection instruments. Results: 93% mother fed exclusively their infant with breast milk whereas 5% fed their infant both with breast milk and formula milk and 2% did not fed their infant with breast milk they gave only formula milk to their infant upto 1.6 months of their infant age. At 3 months, 81% fed exclusively their infant with breast milk only whereas 17% fed their infant both with breast milk and formula milk At 6 months 73% fed exclusively their infant with breast milk whereas 24% fed their infant both with breast milk and formula milk. Conclusions: The sustainability of Exclusive Breast Feeding reduces with the increase in infant’s age. The study had limitations like, the data were collected after their discharge form hospital stay during their follow up visits and by interview technique only which may lead to inaccurate evaluation.